2018
DOI: 10.1016/j.iccn.2017.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an acrylic terpolymer barrier film beneath transparent catheter dressings on skin integrity, risk of dressing disruption, catheter colonisation and infection

Abstract: The application of a barrier film creating a skin-protective polymer layer beneath transparent catheter dressings is associated with less dressing disruptions and skin integrity issues without altering the risk of infectious complications if used in combination with a chlorhexidine-impregnated catheter dressing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…The selected studies included 18 RCTs 19-36 and 2 quasi-experimental studies, 37,38 and all of them were performed in hospital settings. Furthermore, 6 studies were multicentric (≥ 2 hospitals), [19][20][21][22][23]27 14 studies were performed on adults, [20][21][22][23][24][25][27][28][29]31,[33][34][35]38 and 6 studies examined neonates or pediatric populations. 19,26,30,32,36,37 Of the studies with this information, 13 included ICU patients, 19,[21][22][23][24][25][26]29,32,[34][35][36][37] 4 included onco-hematological patients, 27,30,31,33 and 1 included non-ICU patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The selected studies included 18 RCTs 19-36 and 2 quasi-experimental studies, 37,38 and all of them were performed in hospital settings. Furthermore, 6 studies were multicentric (≥ 2 hospitals), [19][20][21][22][23]27 14 studies were performed on adults, [20][21][22][23][24][25][27][28][29]31,[33][34][35]38 and 6 studies examined neonates or pediatric populations. 19,26,30,32,36,37 Of the studies with this information, 13 included ICU patients, 19,[21][22][23][24][25][26]29,32,[34][35][36][37] 4 included onco-hematological patients, 27,30,31,33 and 1 included non-ICU patients.…”
Section: Resultsmentioning
confidence: 99%
“…28 The definition of CRBSI, exit-site and tunnel infections, and adverse events varied across the studies (Appendix 4 online). Also, 5 studies reported CRBSI rates ≥ 2.0 per 1,000 catheter days 21,25,27,30,35 in at least one study group and 2 studies reported CRBSI rates <1.5 per 1,000 catheter days in both groups. 22,23…”
Section: Resultsmentioning
confidence: 99%
“…3A. Twenty-five RCTs [19,20,22,23,31–41,4447,53,5458] (7090 patients) reported the incidence of CRBSI and included all 10 dressings (CHG, BDD, AD, TD, SPU, SDG, SAD, OD, NTD, and HD). The result indicated that TD (odds ratio [OR] 0.35, 95% CrI 0.14, 0.89) was statistically significantly more effective than the other dressings in preventing CRBSI.…”
Section: Resultsmentioning
confidence: 99%
“…Ten RCTs [19,20,31,39–41,43,49,54,51] (1497 participants) reported the CRBSI rate per 1000 catheter-days. Suture + BPU (OR 0.34, 95% CrI 0.27, 0.43) was statistically significantly more effective than dressings alone in reducing the CRBSI rate per 1000 catheter-days.…”
Section: Resultsmentioning
confidence: 99%
“…However, the effect on CR-BSI was not demonstrated and this technology was tested only in CHG impregnated dressing. 91 Both CHG impregnated sponges and CHG-gel dressings were associated with a 60% decrease in the risk of catheter infections including CR-BSIs. 90,92 However, CHG-impregnated sponges and CHG-gel dressings triggered contact dermatitis at a rate of <10/10,000 catheters in adult patients.…”
Section: Dressingmentioning
confidence: 97%